Hemichorea Associated With Non-ketotic Hyperglycemia: A Case Report and Literature Review - Zheng, Wei; Chen, Lin; Chen, Jian-hao; Lin, Xiang; Tang, Yi; Lin, Xiao-juan; Wu, Jing; Lin, Zhao-min; Lin, Jing-yuan (Frontiers in Neurology, 2020)
Objective To study the clinical manifestation, diagnosis, therapy and mechanism of hemichorea associated with non-ketotic hyperglycemia (HC-NH) so as to enhance awareness and avoid misdiagnosis or missed diagnosis of the disease. Methods The paper reported a case of HC-NH and reviewed the clinical features, diagnosis and treatment of HC-NH. Results Hemichorea associated with non-ketotic hyperglycemia was a rare complication of diabetes mellitus，which is commonly seen in elderly women with poorly-controlled diabetes. It was characterized by non-ketotic hyperglycemia, unilateral involuntary choreiform movements, and contralateral basal ganglia hyper-intensity on T1-weighted MR imaging or high density on CT. Blood glucose control was the basal treatment, in combination with dopamine receptor antagonists and benzodiazepine sedative, in controlling hemichorea. Conclusion In clinical practice, the possibility of unilateral chorea should be considered for diabetic patients with poor blood glucose control.